Early patient-reported outcomes from primary hip and knee arthroplasty have improved over the past seven years: an analysis of the NHS PROMs dataset. (1st June 2022) - Sabah, Shiraz A.; Knight, Ruth; Alvand, Abtin; Beard, David J.; Price, Andrew J.
Abstract : Aims: Routinely collected patient-reported outcome measures (PROMs) have been useful to quantify and quality-assess provision of total hip arthroplasty (THA) and total knee arthroplasty (TKA) in the UK for the past decade. This study aimed to explore whether the outcome following primary THA and TKA had improved over the past seven years. Methods: Secondary data analysis of 277, 430 primary THAs and 308, 007 primary TKAs from the NHS PROMs programme was undertaken. Outcome measures were: postoperative Oxford Hip/Knee Score (OHS/OKS); proportion of patients achieving a clinically important improvement in joint function (responders); quality of life; patient satisfaction; perceived success; and complication rates. Outcome measures were compared based on year of surgery using multiple linear and logistic regression models. Results: For primary THA, multiple linear regression modelling found that more recent year of surgery was associated with higher postoperative OHS (unstandardized coefficient (B) 0.15 points (95% confidence interval (CI) 0.14 to 0.17); p < 0.001) and higher EuroQol five-dimension index (EQ-5D) utility (B 0.002 (95% CI 0.001 to 0.002); p < 0.001). The odds of being a responder (odds ratio (OR) 1.02 (95% CI 1.02 to 1.03); p < 0.001) and patient satisfaction (OR 1.02 (95% CI 1.01 to 1.03); p < 0.001) increased with year of surgery, while the odds of any complication reduced (OR 0.97 (95% CI 0.97 to 0.98); p < 0.001). No trend was found for perceived success (p = 0.555). For primary TKA, multiple linear regression modelling found that more recent year of surgery was associated with higher postoperative OKS (B 0.21 points (95% CI 0.19 to 0.22); p < 0.001) and higher EQ-5D utility (B 0.002 (95% CI 0.002 to 0.003); p < 0.001). The odds of being a responder (OR 1.04 (95% CI 1.03 to 1.04); p < 0.001), perceived success (OR 1.02 (95% CI 1.01 to 1.02); p < 0.001), and patient satisfaction (OR 1.02 (95% CI 1.01 to 1.02); p < 0.001) all increased with year of surgery, while the odds of any complication reduced (OR 0.97 (95% CI 0.97 to 0.97); p < 0.001). Conclusion: Nearly all patient-reported outcomes following primary THA/TKA improved by a small amount over the past seven years. Due to the high proportion of patients achieving good outcomes, PROMs following THA and TKA may need to focus on better discrimination of patients achieving high scores to be able to continue to measure improvement in outcomes. Cite this article: Bone Joint J 2022;104-B(6):687–695.